ADCP current measurements (75 kHz) during POSEIDON cruise POS466 - Manfred Kaufmann; Rena Czeschel; Gerd Krahmann; Kai Horst George (PANGAEA, 2024)
A Teledyne RDI Ocean Surveyor systems with 75 kHz transmission frequency were used. Data was processed with a software package developed at GEOMAR following the GO-SHIP standards (Firing and Hummon, 2010). The data was subsequently averaged over one minute intervals and converted to a NetCDF based format.